Autoimmunity in chronic obstructive pulmonary disease: clinical and experimental evidence. (March 2012) - Kheradmand, Farrah; Shan, Ming; Xu, Chuang; Corry, David B
Over the past few decades, neutrophils and macrophages had co-occupied center stage as the critical innate immune cells underlying the pathobiology of cigarette smoke-induced chronic obstructive pulmonary disease and lung parenchymal destruction (i.e., emphysema). While chronic exposure to smoke facilitates the recruitment of innate immune cells into the lung, a clear role for adaptive immunity in emphysema has emerged. Evidence from human studies specifically point to a role for recruitment and activation of pathogenic lymphocytes and lung antigen-presenting cells in emphysema; similarly, animal models have confirmed a significant role for autoimumnity in progressive smoke-induced emphysema. Increased numbers of activated antigen-presenting cells, Th1 and Th17 cells, have been associated with smoke-induced lung inflammation and production of the canonical cytokines of these cells, IFN-γγ and IL-17, correlates with disease severity. These exciting new breakthroughs could open new avenues for developing effective new therapies for smoke-induced emphysema.